Innovation of Solar Powered Irrigation System Based on IoT for Rice Fields in Tempuran Village: Inovasi Sistem Irigasi Tenaga Surya Berbasis IoT untuk Persawahan di Desa Tempuran - Rifqi Firmansyah; Rachmad Syarifudin Hidayatullah; Ali Nur Fathoni; Muhammad Rafli Fahrezy; Nabila Hannunnisa; Amelia Rahmi Wibowo (Muhammadiyah University, Sidoarjo, 2026)
General Background: Agricultural productivity in rural Indonesia is strongly dependent on reliable irrigation systems, while conventional diesel-powered pumps continue to create operational and economic burdens for farmers. Specific Background: Rice fields in Tempuran Village, Mojokerto Regency, experience irrigation instability due to high fuel costs, limited fuel availability, and repeated pump theft, restricting cultivation to two planting seasons annually. Knowledge Gap: Previous studies have commonly examined solar-powered irrigation systems and Internet of Things (IoT)-based agricultural monitoring separately, with limited integration of renewable energy, irrigation security, and farmer capacity development within a single system. Aims: This study aims to develop and evaluate an IoT-based solar-powered irrigation system capable of reducing fossil fuel dependence, improving irrigation reliability, increasing agricultural productivity, and supporting sustainable rural farming. Results: Experimental testing demonstrated that photovoltaic panels generated a maximum power output of approximately 544.6 W and an average daily power of ±342 W, enabling effective battery charging and water pump operation under field conditions. The proposed system is estimated to reduce production costs by up to 40% and support an increase in cultivation frequency from two to three planting cycles per year. Battery analysis showed that a 24 V and 200 Ah battery system could operate pumps for approximately 6.2 hours, while full charging required around 16.5 hours of effective sunlight. Novelty: The study integrates solar photovoltaic irrigation, GPS-based IoT security monitoring, and farmer training into a unified agricultural sustainability framework. Implications: The proposed system contributes to renewable energy adoption, food security, and climate change mitigation while supporting Sustainable Development Goals related to clean energy and sustainable agriculture.